Estudio de la dextrinización y sacarificación del almidón del grano de amaranto (Amaranthus hypochondriacus L.) para la producción de jarabe de glucosa - Barrón Álvarez, Nayeli (Universidad Autónoma Metropolitana, 2017)
The use of enzymes in industrial biotechnological processes becomes increasingly important as new and better products are required to meet highly demanding needs and markets. Different industries such as bakeries, breweries, detergents, wines and fruit juices are developing new enzymatic technologies, as enzymatically hydrolyzed starch arises from the need to substitute certain raw materials to offer products of great competitiveness that generate diverse options in the market , For example: syrups with sugars of greater dissolution power which contribute substances in the preparation of the caramel color that contribute resistance to the thermal discoloration, give body and accentuate the flavors of the fruits, as well as improve the color and textures of some foods. Glucose syrups, in particular, have a huge potential market so they are currently important in the food and pharmaceutical industry. This work describes the use of amaranth starch (Amaranthus hypocondriacus L) to obtain glucose syrups, because corn is currently being exploited and an alternative source is sought for the production of starches for the production of syrups; The hydrolysis conditions were compared to the corn starch. The extraction of amaranth starch was performed by the alkaline method in which 43.83% yield and 96.69% recovery were obtained. The hydrolysis process consisted of two stages 1) dextrinization and 2) saccharification. For the dextrinization, some variables that affect it, such as the concentration of a-amylase, CaCl2, pH, temperature, speed and dextrinization time were tested. Being the experimental conditions for the dextrinization 45 KU of a-amylase, 150 ppm of CaCl2 with pH 6 at a temperature of 90 ° C to 60 rpm during one hour of hydrolysis. Dextrose equivalents (ED) are defined as the amount of reducing sugars present. The ED for dextrinization was 14 with an a-amylase Vmax of 1,284 ± 0.17 g / L * min and a Km of 56,697 ± 0.24 g / L. Similarly, the same variables were evaluated for saccharification with the experimental conditions being 15 U of amyloglucosidase: 30 U of pulalanasa with pH 4.5 at a temperature of 60 ° C for 24 hours of hydrolysis. This resulted in a syrup of 98 g of glucose / L with a Vmax of 1,283 ± 1,03 and a Km of 70,659 ± 0.75. Glucose quantification was measured by the GOD-POD colorimetric method. Amaranth starch proves to be a good alternative for the production of glucose syrups that could be used in the food industry as well as for the production of bioethanol.; La utilización de enzimas en procesos industriales biotecnológicos adquiere cada vez mayor importancia a medida que se requieren nuevos y mejores productos destinados a satisfacer necesidades y mercados altamente exigentes. Diferentes industrias como las de panadería, cervecería, detergentes, vinos y jugos de frutas están desarrollando nuevas tecnologías enzimáticas, así como el almidón hidrolizado enzimáticamente surge de la necesidad de sustituir ciertas materias primas para ofrecer productos de gran competitividad que generan diversas opciones en el mercado, por ejemplo: jarabes con azúcares de mayor poder de disolución las cuales aportan sustancias en la preparación del color caramelo que aportan resistencia a la decoloración térmica, dan cuerpo y acentúan los sabores de las frutas, así como mejoran el color y las texturas de algunos alimentos. Los jarabes de glucosa, particularmente, tienen un enorme mercado potencial por lo que actualmente son importantes en la industria alimentaria y farmacéutica. En este trabajo se describe el uso del almidón de amaranto (Amaranthus hypocondriacus L) para la obtención de jarabes de glucosa, debido a que actualmente se sobre explota al maíz y se busca una fuente alternativa para la obtención de almidón para la producción de jarabes; las condiciones de hidrolisis se compararon con el almidón de maíz. La extracción de almidón de amaranto se realizó por el método alcalino en el cual se obtuvo un 43.83% de rendimiento y un 96.69% de recuperación. El proceso de hidrólisis consistió de dos etapas 1) la dextrinización y 2) la sacarificación. Para la dextrinización se probaron algunas variables que la afectan, como son, la concentración de a-amilasa, CaCl2, pH, temperatura, velocidad y tiempo de dextrinización. Siendo las condiciones experimentales para la dextrinización 45 KU de a-amilasa, 150 ppm de CaCl2 con pH 6 a una temperatura de 90ºC a 60 rpm durante una hora de hidrólisis. Los equivalentes de dextrosa (ED) se definen como la cantidad de azúcares reductores presentes. El ED para la dextrinización fue de 14 con una Vmax de la a-amilasa de 1.284±0.17 g/L*min y una Km de 56.697±0.24 g/L. De manera similar se evaluaron las mismas variables para la sacarificación siendo las condiciones experimentales 15 U de amiloglucosidasa: 30 U de pulalanasa con pH de 4.5 a una temperatura de 60ºC durante 24 horas de hidrólisis. Lo cual resultó en un jarabe de 98 g de glucosas/L con una Vmax de 1.283±1.03 y una Km de 70.659±0.75. La cuantificación de glucosa se midió por medio del método colorimétrico GOD-POD. El almidón de amaranto resulta ser una buena alternativa para la producción de jarabes de glucosa que podría ser utilizado en la industria alimentaria así como para la producción de bioetanol.